MAPK and phenylpropanoid metabolism pathways involved in regulating the resistance of upland cotton plants to Verticillium dahliae - Zhang, Mingli; Ma, Yanjun; Wang, Yuan; Gao, Haifeng; Zhao, Sifeng; Yu, Yu; Zhang, Xuekun; Xi, Hui (Frontiers in Plant Science, 2024)
V. dahliae causes a serious decline in cotton yield and quality, posing a serious threat to the cotton industry. To analyze the defense mechanisms of cotton in response to V. dahliae infection, we compared the defense responses of two upland cotton cultivars from Xinjiang (JK1775, resistant; Z8,susceptible) using transcriptome sequencing at different infection stages. The results revealed a significant differential expression of genes in the two cotton cultivars post V. dahliae infection, with the number of DEGs in JK1775 being higher than that in Z8 at different infection stages of V. dahliae.Interestingly, the DEGs of both JK1775 and Z8 were enriched in the MAPK signaling pathway in the early and late stages of infection. Importantly, the upregulated DEGs in both cultivars were significantly enriched in all stages of the phenylpropanoid metabolic pathway. Some of these DEGs were involved in the regulation of lignin and coumarin biosynthesis, which may be one of the key factors contributing to the resistance of upland cotton cultivars to V. dahliae in Xinjiang. Lignin staining experiments further showed that the lignin content increased in both resistant and susceptible varieties after inoculation with V. dahliae. This study not only provides insights into the molecular mechanisms of resistance to Verticillium wilt in Xinjiang upland cotton but also offers important candidate gene resources for molecular breeding of resistance to Verticillium wilt in cotton.